Selected poems - Updike, John 1932-2009 (Borzoi book, 2015)
"A beautiful Selected volume of this masterly writer's poetry, giving us five decades of witty, intimate, and moving poems with the cumulative force of an autobiography in verse. Though John Updike is widely known as one of America's greatest writers of prose, he began and ended his career with books of poems, and between them published six other accomplished collections. Now, six years after Updike's death, Christopher Carduff has selected the best of his lifework in poetry: 132 of his most significant and accomplished poems, from precocious undergraduate efforts to well-known anthology classics to the late-life mastery of the blank-verse sonnet sequence "Endpoint." Art, nature, popular culture, foreign travel, erotic love, and personal history...these recurring topics provided the poet ever-surprising occasions for metaphysical wonder and matchless verbal invention. His Selected Poems is, as fellow-poet Brad Leithauser writes in his introduction, a celebration of American life in the second half of the twentieth century, and no one but Updike "captured upon the page, in prose and in poetry, so much of this passing pageant. That he did so with brio and delight and nimbleness is yet another reason to celebrate our noble celebrant.""..